Psychological Interventions for Recurrence Prevention in Adolescent Depression: A Systematic Review - Chonnakarn Jatchavala; Stella Chan (Journal of Health Science and Medical Research (JHSMR), 2018)
Objective: To determine the effectiveness of psychological interventions in depressive adolescents to prevent recurrent depressive episodes. Material and Methods: English databases, including Embase, Medline, Global Health, and PsychINFO, were searched for studies that examined the effectiveness of psychological interventions in preventing recurrent depression. Eight articles were found in the electronic databases and 4 studies were found from a manual search. Methodological quality was assessed using the Cochrane Collaboration’s tool. Results: One quasi-randomized control trial and 11 randomized control trials met the inclusion criteria. A systematic review of the 12 studies was conducted. The studies involved 1,641 participants that represented different effects of recurrence prevention interventions at 6, 9, 12, 24, and 33 months following treatment completion. Cognitive behavioral therapy (CBT) group intervention showed effectiveness in recurrence prevention in depressive adolescents in 6-33 months. Supportive psychotherapy and family therapy also prevented recurrent depression at 24-month follow-up, while psychodynamic/psychoanalytic psychotherapy and interpersonal psychotherapy could prevent recurrence in depressive adolescents for 12 months following completion of the intervention. Conclusion: Among the psychological interventions studied in the included articles, CBT group intervention showed the greatest long-term effect since group CBT could prevent recurrent depression in adolescents up to 33 months.